2012
DOI: 10.1016/j.ijnt.2012.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Role of repeat CT scans in the management of traumatic brain injury

Abstract: Background In trauma practice, there are no guidelines on the necessity or value of repeat CT scan. The purpose of the present study was to determine the role of serial CTs in demonstrating changes in intracranial lesions and the influence on management. Methods In this study, 201 patients of traumatic brain injury were followed with serial CT scans for a maximum of up to 5 scans. The presence of different types of intracranial lesions at each CT scan as well as the evolution of lesions was recorded. The dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…In some studies, it has been advocated that if the first CT scan is done too early after the injury, it can fail to detect the early head injury. They recommended an interval of routine repeat scans to be 12–24 hours; others recommend 8 hours for the repetition [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, it has been advocated that if the first CT scan is done too early after the injury, it can fail to detect the early head injury. They recommended an interval of routine repeat scans to be 12–24 hours; others recommend 8 hours for the repetition [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Doddamani et al 27. found new lesions were present in 5.5% of the second and third CT scans, and observed a change in management in 23% of patients, of which almost half the changes were due to radiological differences alone.…”
Section: Role Of Computed Tomographymentioning
confidence: 98%
“…25 Some radiology departments perform repeat CT examinations on patients to monitor changes in injuries, in particular vascular or infectious complications, 26 however, repeat imaging is not routine and should be undertaken at the request of neurologists or other appropriate clinicians. Doddamani et al 27 found new lesions were present in 5.5% of the second and third CT scans, and observed a change in management in 23% of patients, of which almost half the changes were due to radiological differences alone. However, a recent metaanalysis concluded that repeat CT in traumatic brain injury patients changes the management in only a minority of patients, hence the use remains controversial.…”
Section: Role Of Computed Tomographymentioning
confidence: 98%
“…Limitations of noncontrast CT include a poor sensitivity for small hemorrhages, diffuse axonal injury (DAI), arterial dissection, and vascular damage 6 , 7 . In particular, in TBI patients with secondary progression of initially undetected small cerebral hemorrhages might cause a decline in the functional status of the patient, which motivates the need of early detection of these traumatic lesions 8 …”
Section: Introductionmentioning
confidence: 99%